Analysis of Stakeholder Perception On Transparency, Accountability And Effectivity In School Operational Assistance Funds Management For Junior High School Level In North Aceh Regency - Dahliana; Naz’aina; Khaddafi, Muammar (TALENTA Publisher, Universitas Sumatera Utara, 2021)
This study aims to analyze the differences in perceptions of internal stakeholders and external stakeholders about transparency, accountability and effectivity in the management of School Operational Assistance (BOS) funds in 97 State junior high schools in North Aceh Regency. The sample in this study is divided into two groups, they are the internal stakeholders group who is consisting of 97 principals, 97 vice principals, 97 treasurers and 97 committee chairs which is obtained by the saturated sample method, while external stakeholders are 392 guardians of students which is obtained from the slovin formula by using random sampling method. The types of data used are primary data in the form of respondents' answers to research questionnaires, observations and interviews and secondary data are literature studies and Basic Education Data for 97 State junior high schools in North Aceh Regency. The data analysis method used is the Mann Whitney Test. The results of this study found that there is a significant difference between the perceptions of internal stakeholders and external stakeholders about transparency, accountability and effectivity of BOS fund management at State Junior High Schools in North Aceh Regency